Incidence, causes and risk factors of vision loss in rural Southern China: 6-year follow-up of the Yangxi Eye Study - Zhao, Xinyu; Lin, Jianqiang; Yu, Shanshan; Xie, Liqiong; Jin, Ling; Xiong, Kun; Tsui, Ching-Kit; Xu, Yue; Wu, Benjuan; Liu, Bin; Wang, Wei; Congdon, Nathan; et al. (British journal of ophthalmology, 2023)
PurposeTo report the 6-year incidence, causes and risk factors for vision loss (visual impairment (VI) and blindness), among elderly adults in rural southern China.MethodsPopulation-based, cohort study. Initiated in 2014, the study recruited participants aged 50 and older using random cluster sampling from Yangxi County. All eligible participants were invited to attend interviews and comprehensive eye examinations at the 6-year follow-up between November 2020 and March 2021. The WHO categories of vision loss were used to define incident cases of VI (3/60≤VA <6/12), moderate-to-severe VI (MSVI) (3/60≤VA<6/18) and blindness (VA <3/60) in the better-seeing eye.ResultsAmong the 5825 baseline participants, 3187 (64.4%) of 4946 surviving subjects participated in the 6-year follow-up. Based on presenting and best-corrected VA, respectively, the crude incidence rate of blindness was 0.8% (95% CI 0.5% to 1.1%) vs 0.3% (95% CI 0.1% to 0.5%), for MSVI 6.7% (95% CI 5.7% to 7.6%) vs 4.6% (95% CI 3.8% to 5.4%) and for any VI 16.1% (95% CI 14.5% to 17.6%) vs 12.9% (95% CI 11.6% to 14.1%). Cataract (48.3%) and refractive errors (44.4%) were the most common causes of vision loss. Factors significantly associated with greater incident vision loss were older age, female sex, less education, living alone and longer axial length (all p<0.05).ConclusionsSubstantial work is still required to reduce avoidable vision loss in rural China. Screening outreach and efforts to improve awareness which target the poorer and less educated are urgently needed to reduce the growing unmet need for eye care due to ageing.